Stuttering and hearing loss - Rathna N; Nataraja NP (Journal of All India Institute of Speech and Hearing, 1972)
The story often been recounted of the American Indian who stood up to stuttera defiance to Wendell Johnson's paper "The Indian's have no word for it", at aconference of the American Speech and Hearing Association. Mention has alsobeen made that after Robert West had hypothesized the impossibility of a diabeticstuttering a gentleman in the audience announced that he was a diabetic whostuttered. The Indian was a fake and was part of a practical joke ; the diabetic wasnot. The main point is that the exception proves that rule is a good repartee atcasual conversation, but it is irrelevent in scientific explanations. It is importantthat any theory which tries to be comprehensive explains or at least takes note of theexceptions. The theory should not only include and explain exceptions to the theorydirectly but it should also explain exceptions to the inferences that are drawndirectly from the theory. Thus the exceptions when explained helps to expand thepre-view of the theory or when it is not explained limits the scope and strength of thetheory. While it is generally conceded that a theory works only within the limitedframework in which it is formed, theories when propounded sound dangerouslycomprehensive. Therefore the exceptions become extremely important in challengingsuch postures of comprehensiveness.